Standards for the Epidemiological Investigation of Measles and Rubella Foci - O. V. Tsvirkun; N. T. Tikhonova; A. G. Gerasimova; N. V. Turaeva; L. A. Barkinkhoeva; N. I. Briko (Эпидемиология и вакцинопрофилактика)
In practical medicine, standards for the provision of therapeutic and preventive care have been used for a long time, but in epidemiology this concept has not yet been reflected in regulatory documents. Epidemiologists need a standard of epidemiological investigation of cases of measles and rubella infection, which must be eliminated. The use of specific terms, the interaction of specialists of various profiles, the emphasis on the classification of the case – «local», «imported from the territory of another state», «imported from another territory of Russia», the need to assess the degree of secondary spread of infection imposes its own characteristics on the epidemiological investigation of measles and rubella cases. The use of standards would optimize this process, prevent errors and minimize the time of localization and elimination of the outbreak.The standard of epidemiological investigation of measles and rubella cases consists of three independent sections, such as examination of the focus, laboratory examination of patients and directions of information flows between medical organizations and organizations of the sanitary and epidemiological service. The main parameters of the epidemiological examination of a measles/rubella outbreak are — person, time, place, contacts; this is the sequence provided for when collecting and analyzing identification and epidemiological information about the patient. The laboratory research section determines the implementing organization, the type of clinical sample, taking into account the research method, the timing of taking the material for research, the volume, frequency, time of delivery of the material to the laboratory and the timing of obtaining the result. The epidemiological investigation ends with the execution of a number of documents, such as the «Map of the epidemiological examination of the focus of an infectious disease», «The Act of investigation with the establishment of cause-and-effect relationships», as well as the control of anti-epidemic measures. The model of the direction of information flows provides for the order of interaction of various organizations: the movement of reports, clinical samples, research results and «Maps of epidemiological examination of the focus of an infectious disease», etc., as well as regulated deadlines for the implementation of measures. Since the standard is a single, binding scheme of actions, the practical application of the standard of epidemiological investigation of measles and rubella will allow collecting and processing information in a single format throughout the country.